Produção e caracterização de ligas do sistema Al-Co-Fe- Cr e aplicações como recobrimentos para barreiras térmicas - Wolf, Witor (2015)
Since the discovery of the quasicrystalline alloys by D. Schechtamn in 1984, many research has been done in terms of coating application of these materials and their intermetallic approximants due to their physical and transport properties as: high hardness, low friction coefficient, low superficial adhesion energy, high oxidation resistance and low thermal conductivity. The low thermal conductivity combined with the thermal expansion in the same range of the usual metallic materials used as substrates in coatings make these alloys as potential substitutes for the traditional ceramics thermal barrier coatings. The alloy Al71Co13Fe8Cr8 has been studied in terms of thermal barrier applications. This alloy presents interesting properties and characteristics for this application. However, the information about this alloy on the literature is scarce and contradictory. In this sense, in the present work, the Al71Co13Fe8Cr8 alloy was selected for coating fabrication aiming to obtain a consistent structural characterization of this alloy. Results show that the Al71Co13Fe8Cr8 alloy is not a quasicrystalline forming composition. It is actually composed by two intermetallic phases, one hexagonal and the other monoclic, Al5Co2 and Al13Co4 respectively, which are approximant phases of the decagonal QC with the interesting physical and transport properties presented by the quasicrystalline phase. The coatings were also studied in terms of the interdifusion phenomena between the coating and a steel substrate at high temperatures. Alloys around the Al71Co13Fe8Cr8 compositional range were also fabricated in order to evaluate the phase formation on the aluminum rich region of the Al-Co-Fe-Cr system. Several intermetallic phases were observed, most of them quaternary extensions of Al-Co intermetallic phases. A quasicrystalline phase was also observed in one of the studied compositions.